Sindrom Putus Steroid Anabolik Androgenik: Tinjauan untuk Praktisi Kesehatan: Tinjauan Pustaka - -, William; Angellee, Jesselyn (PT Kalbe Farma Tbk., 2026)
The non-medical use of anabolic androgenic steroid (AAS) has significantly increased among athletes, bodybuilders, and individuals who focus on physical performance as well as body aesthetics. Although AAS has certain therapeutic benefits, use outside of medical supervision can lead to AAS withdrawal syndrome. This condition is characterized by physical and psychological symptoms, such as fatigue, decreased libido, anxiety, depression, and sleep disturbances. Its primary mechanism is the suppression of the hypothalamic–pituitary–gonadal (HPG) axis, which reduces endogenous testosterone production after discontinuation of AAS. Disruption of this axis not only decreases endogenous testosterone production but also alters gonadotropin hormone dynamics and androgen receptor responsiveness. Several risk factors, such as high doses, prolonged duration of use, specific usage patterns (cycling, stacking, pyramiding), and a history of psychological disorders, may exacerbate withdrawal symptoms. Management of AAS withdrawal syndrome includes short-term hormonal therapy, agents that stimulate endogenous testosterone production, psychological interventions, and physical rehabilitation. A multidisciplinary approach and close medical monitoring are required to restore endocrine function, prevent complications, and improve the patient’s psychological well-being. This paper provides a comprehensive overview to assist healthcare practitioners in recognizing, diagnosing, and appropriately managing AAS withdrawal syndrome.